2015
DOI: 10.3324/haematol.2014.118075
|View full text |Cite
|
Sign up to set email alerts
|

Risk of bleeding and use of platelet transfusions in patients with hematologic malignancies: recurrent event analysis

Abstract: This study is a further analysis of the TOPPS trial data and assesses patients' baseline characteristics at enrolment, burden of thrombocytopenia, presence of fever and presence of minor hemorrhage as potential risk factors for WHO grade 2 to 4 bleeding. Recurrent event analyses have been used to allow assessment of bleeding over the 30-day trial period and to account for multiple bleeds per patient. MethodsDetails of the UK and Australian TOPPS randomized trial have been published previously .2,8,10 Six hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 22 publications
1
56
1
Order By: Relevance
“…As described, increased overall risk for bleeding correlated with treatment stratum, profoundly low platelet counts (#5 3 10 9 /L), hematocrit of #25%, INR .1.2, and aPTT .30 seconds. The findings echo those reported by others in demonstrating that a large percentage of patients with hypoproliferative thrombocytopenia experience grade 2A bleeding 16 and a minority experience grade 3 and/or 4 bleeding. Given the attendant risks of platelet transfusion (adverse reactions, including septic transfusion reactions), further exploration of the impact of treatment-related risk factors, and careful assessment of posttransfusion impact on bleeding is encouraged.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…As described, increased overall risk for bleeding correlated with treatment stratum, profoundly low platelet counts (#5 3 10 9 /L), hematocrit of #25%, INR .1.2, and aPTT .30 seconds. The findings echo those reported by others in demonstrating that a large percentage of patients with hypoproliferative thrombocytopenia experience grade 2A bleeding 16 and a minority experience grade 3 and/or 4 bleeding. Given the attendant risks of platelet transfusion (adverse reactions, including septic transfusion reactions), further exploration of the impact of treatment-related risk factors, and careful assessment of posttransfusion impact on bleeding is encouraged.…”
contrasting
confidence: 48%
“…5,6,16 Our secondary analysis demonstrated that patients in the AUTO stratum had lower risk for bleeding and thus represent a patient population for which a therapeutic-only platelet transfusion approach could be considered. However, even patients in the AUTO stratum had a high risk of bleeding at platelet counts #5 3 10 9 /L.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous extravasation of red cells occurred in patients with prolonged deep thrombocytopenia. In agreement with this finding, a secondary analysis of the TOPPS study revealed that a greater number of days with a platelet count <10 9 10 9 /l is associated with haemorrhage (Stanworth et al, 2015b). However, although a disturbed vascular lining is apparently an important risk for bleeding, surprisingly, laboratory tests do not take vascular integrity into account for transfusion management.…”
Section: Discussionmentioning
confidence: 78%
“…26,28,29 The risk of bleeding is increased in patients taking ibrutinib in combination with aspirin and new oral anticoagulants, and concurrent warfarin therapy is contraindicated. 30 To our knowledge there are no data supporting the use of PPI prophylaxis in patients on ibrutinib and EviQ guidelines do not mention PPI use in these patients.…”
Section: Anti-platelet Agents and Anticoagulantsmentioning
confidence: 95%
“…Minor bleeding on ibrutinib is common, but grade 3 or higher bleeding rates attributable to the drug are low, and the incidence of GI bleeding specifically is not well documented . The risk of bleeding is increased in patients taking ibrutinib in combination with aspirin and new oral anticoagulants, and concurrent warfarin therapy is contraindicated . To our knowledge there are no data supporting the use of PPI prophylaxis in patients on ibrutinib and EviQ guidelines do not mention PPI use in these patients.…”
Section: Literature Reviewmentioning
confidence: 99%